The PYRIN domain-only protein POP3 inhibits ALR inflammasomes and regulates responses to infection with DNA viruses. - Khare, S; Ratsimandresy, R; de Almeida, L; Cuda, C; Rellick, S; Misharin, A; Wallin, M; Gangopadhyay, A; Forte, E; Gottwein, E; Perlman, H; Reed, J; et al. (2014)
The innate immune system responds to infection and tissue damage by activating cytosolic sensory complexes called 'inflammasomes'. Cytosolic DNA is sensed by AIM2-like receptors (ALRs) during bacterial and viral infections and in autoimmune diseases. Subsequently, recruitment of the inflammasome adaptor ASC links ALRs to the activation of caspase-1. A controlled immune response is crucial for maintaining homeostasis, but the regulation of ALR inflammasomes is poorly understood. Here we identified the PYRIN domain (PYD)-only protein POP3, which competes with ASC for recruitment to ALRs, as an inhibitor of DNA virus-induced activation of ALR inflammasomes in vivo. Data obtained with a mouse model with macrophage-specific POP3 expression emphasize the importance of the regulation of ALR inflammasomes in monocytes and macrophages.